The polynomial method for list-colouring extendability of outerplanar graphs - Gordinowicz, Przemysław (Ars mathematica contemporanea, 2021)
We restate theorems of Hutchinson On list-coloring extendable outerplanar graphs, Ars Math. Contemp. 5 (2012), 171–184, doi:10.26493/1855-3974.179.189 on list-colouring extendability for outerplanar graphs in terms of non-vanishing monomials in a graph polynomial, which yields an Alon-Tarsi equivalent for her work. This allows to simplify her proofs as well as obtain more general results.
Keywords: Alon-Tarsi number; Alon-Tarsijevo število; barvanje z izbranim naborom barv; barvnost; list colouring; outerplanar graph; paintability; zunanje ravninski graf